Effect of Moisture Damage on Hot Asphalt Mixture: A Scientific Metric ‎Analysis and Bibliometric Review (Journal of University of Babylon for Engineering Sciences, 2023)
Asphalt concrete or a dense graded mixture is an acceptable additive used to improve the performance and longevity of asphalt road materials (DGM). The use of various recycled materials as fillers is one of many diverse strategies used to reduce the impact of moisture damage on the pavement, as well as to reduce cost, improve road efficiency, and reduce the harmful impact of solid waste by recycling it. Alkalinity, coarse surface roughness, fine particles preventing air gaps, increasing the bonding between asphalt slurry and aggregate, and improving moisture sensitivity are all characteristics of fillers.It can be constructed so that it works well as a filler to increase the quality and durability of the pavement. It is essential to understand previous research pappers and investigations. The VOS Viewer was used to visualize the data in early tests. Keyword data was downloaded in Excel format from the Dimension, Web of Science, and Scopus websites. Lists these terms, authors, and researchers by country. With the help of the terms (hot asphalt), (asphalt sensitivity to moisture), (additives) and (wet damage), the researcher was able to conduct a study that was identical to his or her study.